BBS1 is involved in retrograde trafficking of ciliary GPCRs in the context of the BBSome complex - Nozaki, Shohei (PLoS One, 2018)
Protein trafficking within cilia is mediated by the intraflagellar transport (IFT) machinery composed of large protein complexes. The BBSome consists of eight BBS proteins encoded by causative genes of Bardet-Biedl syndrome (BBS), and has been implicated in the trafficking of ciliary membrane proteins, including G protein-coupled receptors (GPCRs), by connecting the IFT machinery to cargo GPCRs. Membrane recruitment of the BBSome to promote cargo trafficking has been proposed to be regulated by the Arf-like small GTPase ARL6/BBS3, through its interaction with the BBS1 subunit of the BBSome. We here investigated how the BBSome core subcomplex composed of BBS1, BBS2, BBS7, and BBS9 assembles and interacts with ARL6, and found that the ARL6–BBS1 interaction is reinforced by BBS9. BBS1-knockout (KO) cells showed defects in the ciliary entry of other BBSome subunits and ARL6, and in ciliary retrograde trafficking and the export of the GPCRs, Smoothened and GPR161. The trafficking defect of these GPCRs was rescued by the exogenous expression of wild-type BBS1, but not by its mutant lacking BBS9-binding ability. Our data thus indicate that the intact BBSome is required for retrograde trafficking of GPCRs out of cilia.